Efektifitas Ruqyah Syar'iyyah dan Pengobatan Medis: Studi di Kasus Pada Gangguan Kesehatan Mental - Muhammad Faisal; Pradipta Bagas Daniswara; Novian Tri Wahyudi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The community's adoption of Ruqyah Syar'iyyah as an alternative therapy for mental health issues is what spurred this investigation. The research aims to explore the effectiveness of both Ruqyah Syar'iyyah and medical treatment in addressing mental health disorders and to compare the impact on patients. A case study strategy in conjunction with a qualitative technique was used. In-depth interviews with patients suffering from mental health conditions like anxiety, stress, and depression as well as with Ruqyah Syar'iyyah practitioners and medical experts were used to gather data. The findings indicate that Ruqyah Syar'iyyah provides spiritual tranquility, mental fortitude, and increased faith in patients, while medical treatment helps manage symptoms and correct chemical imbalances in the brain. The combination of both approaches yielded significant positive impacts on patients, including reduced symptoms, improved quality of life, and faster recovery. This study concludes that a holistic approach integrating Ruqyah Syar'iyyah and medical treatment can serve as an effective alternative in addressing mental health disorders.